PENGARUH UKURAN PERUSAHAAN, OPINI AUDIT, UKURAN KAP DAN AUDIT TENURE TERHADAP AUDITOR SWITCHING - Galih Chandra Kirana; Muhamad Ridwan Indriansyah (Jurnal Liabilitas, 2022)
The Purpose of this research is to know the influence of company size, audit opinion, the size of size of public accountant firm and the tenure audit of the SWITCHING auditor to the IDX-listed manufacturing company, where the total length of the Audit Alliance as the tenure audit indicator , and the natural logarithm of the company's total assets as the company's size indicator, this research is a type of causal research, which uses population data from 166 companies listed on the Indonesia stock Exchange 2014-2018 The retrieval methods used in this study are purposive sampling and obtained data that passed the test as much as 43 company samples and 215 observation counts. The Data used is the financial statement of each of the sample company Maing published through the site www.idx.co.id . The results showed that the company's size partially did not have any significant effect on the auditor switching, the partial audit opinion has no significant effect on the auditor switching, size of public accountant firm has no significant effect on the auditor switching and Audit tenure partially significant effect on auditor switching. Keywords: Company Size, Audit Opinion, Size of Public Accountant Firm, Audit Tenure, Auditor Switching